Building an authentic leadership image - Criswell, Corey (Center for Creative Leadership, 2008)
Your image can be either an asset or a liability for you as a leader. Image building is neither superficial nor unimportant. It's not about creating a false image, but recognizing genuine aspects of yourself that should be coming across to other people--but aren't. Crafting your image requires you to gain a clear picture of the image people are currently perceiving, decide what image you would like to portray, and develop the skills to close the gap.
"For the practicing manager"--Cover. - Includes bibliographical references (pages 28-29). - Print version record
Keywords: Authentic leadership -- Handbooks, manuals, etc; Leadership -- Handbooks, manuals, etc; Self-presentation -- Handbooks, manuals, etc; Leadership; Guides, manuels, etc; Présentation de soi; Guides, manuels, etc; BUSINESS & ECONOMICS; Leadership; Leadership; Authentic leadership; Self-presentation; handbooks; manuals (instructional materials); Handbooks and manuals; Guides et manuels